Phylogenetic Relationships of Pseudorasbora, Pseudopungtungia, and Pungtungia (Teleostei; Cypriniformes; Gobioninae) Inferred from Multiple Nuclear Gene Sequences. (10th September 2013) - Kim, Keun-Yong; Ko, Myeong-Hun; Liu, Huanzhang; Tang, Qiongying; Chen, Xianglin; Miyazaki, Jun-Ichi; Bang, In-Chul
Abstract : Gobionine species belonging to the genera Pseudorasbora, Pseudopungtungia, and Pungtungia (Teleostei; Cypriniformes; Cyprinidae) have been heavily studied because of problems on taxonomy, threats of extinction, invasion, and human health. Nucleotide sequences of three nuclear genes, that is, recombination activating protein gene 1 ( rag1 ), recombination activating gene 2 ( rag2 ), and early growth response 1 gene ( egr1 ), from Pseudorasbora, Pseudopungtungia, and Pungtungia species residing in China, Japan, and Korea, were analyzed to elucidate their intergeneric and interspecific phylogenetic relationships. In the phylogenetic tree inferred from their multiple gene sequences, Pseudorasbora, Pseudopungtungia and Pungtungia species ramified into three phylogenetically distinct clades; the " tenuicorpa " clade composed of Pseudopungtungia tenuicorpa, the " parva " clade composed of all Pseudorasbora species/subspecies, and the " herzi " clade composed of Pseudopungtungia nigra, and Pungtungia herzi . The genus Pseudorasbora was recovered as monophyletic, while the genus Pseudopungtungia was recovered as polyphyletic. Our phylogenetic result implies the unstable taxonomic status of the genus Pseudopungtungia .